AHMED BIN SHAHEEN ALCYPRS (1053 A.H) THE MOST PROMINENT TRADITIONAL ARTS IN HIS OFFICE - Youssef Hammad Jubeir Al-Harbi , Prof. Dr. / Firas Abdul Rahman Ahmed Al- Najjar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Alhahina was poets of Damascus in the Ottoman era, Aban atheist century AH, described his hair Badhupth, and it was very tenderness, and the lack of his hair was able to highlight his star in the middle of the poets of his time brilliant, was the poets glorified in the later. He excelled in most of the poetic purposes, such as praise, spinning, lament, satire and description. quality in the poetry of that era.